2014
DOI: 10.1007/s00428-014-1585-7
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 cytological index can distinguish well-differentiated from poorly differentiated pancreatic neuroendocrine tumors: a comparative cytohistological study of 53 cases

Abstract: The Ki-67 labeling index has been found to bear prognostic significance in gastrointestinal neuroendocrine tumors (NETs), and it was recently incorporated in NET histological grading. Nevertheless, a reliable preoperative determination of NET grading could be useful in clinical practice. The aim of this study is to compare the results of Ki-67 labeling index, as measured on cytological samples and on surgical specimens of patients with pancreatic NETs (P-NETs). We also investigated whether concordance might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 26 publications
0
34
1
3
Order By: Relevance
“…This is also largely described in the recent literature [2,15,16,[21][22][23][24] and seems to be due to tumour heterogeneity. Yang et al [25], studying tumour heterogeneity on 45 liver metastases from pNETs, showed that G1 tumours are relatively homogeneous, whereas 91% of their G2 cases harboured areas with <3% Ki67-LI.…”
Section: Progression-free Survivalmentioning
confidence: 98%
See 1 more Smart Citation
“…This is also largely described in the recent literature [2,15,16,[21][22][23][24] and seems to be due to tumour heterogeneity. Yang et al [25], studying tumour heterogeneity on 45 liver metastases from pNETs, showed that G1 tumours are relatively homogeneous, whereas 91% of their G2 cases harboured areas with <3% Ki67-LI.…”
Section: Progression-free Survivalmentioning
confidence: 98%
“…Since 2014 and the publication of our first paper [17], a few groups have done comparative studies between the Ki67-LI obtained on FNA and the corresponding resection specimens [2,9,15,16,[20][21][22][23][24]. Our study represents the largest to date, not only in terms of comparison of grading, but also in terms of Ki67-LI absolute values, between cytology and corresponding resection specimens, studying the influence of tumour size, the number of counted cells on FNA and overall and progression-free survival.…”
Section: Progression-free Survivalmentioning
confidence: 99%
“…Li et al in their meta-analysis showed that Ki67 LI assessment based on cytological samples had a pooled sensitivity of 64% for detection of G2/G3 vs. G1 tumours [19]. Carlinfante et al showed that Ki67 LI in cytological sample had poor sensitivity for detection of G2 NET, but allowed perfect distinction of NET and NEC [83]. Change of grade of NET is not rare at the stage of synchronous and especially metachronous metastatic disease [15].…”
Section: Ki67 LI Heterogeneity In the Context Of Csmentioning
confidence: 99%
“…Thus, it is not always easy to identify a relation between the tracer uptake and histopathologic indices of tumor proliferation, which can guide therapeutic management. Multiple numbers of lesions with variable tracer uptake at different parts of the tumor, especially in the same organ, may cause the biopsy not to fully reflect in vivo tumor heterogeneity (5,6), thus leading to inaccurate Ki67 values. Likewise, tumors with lower proliferation are supposed to be less aggressive and vice versa, but that is not always the case.…”
mentioning
confidence: 99%